Evaluating effective spare-parts inventory management for equipment reliability in manufacturing industries - Baluch, Nazim Hussain; Abdullah, Che Sobry; Mohtar, Shahimi (IISTE, 2013)
The spare part management function is critical from an operational perspective especially in asset intensive industries such as refineries, chemical plants, paper mills, automotive manufacturing, and oil mills.Given the determinants like demand, unpredictability, part substitution, and tight control on spare parts inventory coupled with high service level expectations; the exigency of spare parts management in manufacturing operations cannot be underrated.In most organizations, a constant scrimmage persists over the stocking, ordering, and maintaining of products required by maintenance and operations. The Materials Management and Purchasing functions are often vied against Maintenance, Facilities, Engineering, and Operations with respect to; the number and types of stock keeping units, capital and critical spares, obsolete inventory, inventory investment, and turnover and program operation. This paper evaluates best practices in the Maintenance Repairs & Overhauls, discusses the ABC classification scheme, and elaborates on the role of maintenance storeroom as service provider.